Persepsi Mahasiswa Terhadap Interprofessional Education Berbasis Kesehatan Haji - Wijaya, Dhani (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2023)
Background:The Faculty of Medicine and Health Sciences, State Islamic University of Maulana Malik Ibrahim implements interprofessional education based on Hajj health to initiate teamwork between pharmacy students and medical students. This is in an effort to help prospective pilgrims achieve the requirements of istitha'ah, namely the ability of pilgrims from a health perspective so that they can perform the pilgrimage. It is important to pay attention to the health of prospective pilgrims considering the risk of degenerative diseases in pilgrims so that it can increase the death rate of pilgrims while performing the pilgrimage. Interprofessional education can help monitor the health of pilgrims with collaborative work between the fields of medicine and pharmacy. Student perceptions of the implementation of Hajj health-based interprofessional education is one of the important parameters in evaluating the implementation of Hajj health-based interprofessional education to be able to formulate improvements in the next program. Aim of the study: This study aims to assess the perceptions of medical students and pharmacy students towards the Hajj health-based interprofessional education program. Method: The research design is descriptive qualitative with purposive sampling technique. The inclusion criteria were students taking the Hajj health-based interprofessional education program in 2021 and the exclusion criteria were students who did not fill out a complete questionnaire. The research instrument was a Likert scale questionnaire adopted from Student Perceptions of Interprofessional Clinical Education. Data presented using Microsoft Office Professional Plus Excel 2016. Results: The study sample consisted of 79 pharmacy students and 34 medical students with the majority being female. Study participants aged 19-24 years. as many as 88.61% of pharmacy students have a good perception of hajj health-based interprofessional education, as well as 91.18% of medical students. Conclusion: The majority of students in the study had a good perception of Hajj health-based interprofessional education. The existence of students who have a bad perception of this program requires a follow-up plan so that the program objectives can be achieved to spur inter-professional collaboration and provide maximum contribution to the health of the hajj.